Integration of emerging equity markets. A systematic review - Thapa, Chandra (Cranfield University, 2007)
Emerging equity markets have attracted foreign investor by their higher returns and prospect of superior risk diversification benefits. In light of increasing flow of equity portfolio investments into these economies and their subsequent integration with equity markets of developed world, studies have not only shown concern over the reduction in the long term risk diversification benefits, but also there may be less of increase in the original price of securities. Local economy initiates formal financial liberalisation measures to integrate with world capital markets. However, removal of regulatory restrictions may not attract foreign investments in the presence of other indirect barriers and emerging markets specific risks. Also, the process of financial liberalisation is time varying and not one off event. This creates difficulty in pin pointing the exact date of liberalisation. These complexities cause difficulties in the development of dynamic models for pricing securities in emerging markets and measuring the impact of integration. However, with the removal of direct and indirect barriers to foreign investments, these markets are showing greater integration with world markets. With increasing integration emerging markets are becoming more susceptible to global risk factors. Higher degree of integration should reduce cost of equity capital (expected return) and increase the correlation of returns with developed markets. However, empirical works report the reduction in cost of capital to be lower than predicted by asset pricing models. It is also challenging to measure the degree of market integration because of the constant structural changes observed in emerging markets. Countries have even been found to exhibit segmentation over time. Hence, in the context of asset pricing models the findings on the degree of integration are inconclusive and conflicting.